2018
DOI: 10.4049/jimmunol.1700614
|View full text |Cite
|
Sign up to set email alerts
|

ABIN2 Function Is Required To Suppress DSS-Induced Colitis by a Tpl2-Independent Mechanism

Abstract: The A20-binding inhibitor of NF-κB 2 (ABIN2) interacts with Met1-linked ubiquitin chains and is an integral component of the tumor progression locus 2 (Tpl2) kinase complex. We generated a knock-in mouse expressing the ubiquitin-binding–defective mutant ABIN2[D310N]. The expression of Tpl2 and its activation by TLR agonists in macrophages or by IL-1β in fibroblasts from these mice was unimpaired, indicating that the interaction of ABIN2 with ubiquitin oligomers is not required for the stability or activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This implies that physiological variations in the amounts of SINT-speckle proteins can already affect speckle formation. Regulation of ABIN2 protein levels occurs in the presence of increased glucose levels or by the kinases TPL2 or IKKα/β (Chen et al., 2013, Leotoing et al., 2011, Nanda et al., 2018), and it will thus be interesting to investigate whether these situations will affect the formation of SINT-speckles. The formation of inducible SINT-speckles is regulated by several mechanisms, as schematically shown in Figure 9B.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that physiological variations in the amounts of SINT-speckle proteins can already affect speckle formation. Regulation of ABIN2 protein levels occurs in the presence of increased glucose levels or by the kinases TPL2 or IKKα/β (Chen et al., 2013, Leotoing et al., 2011, Nanda et al., 2018), and it will thus be interesting to investigate whether these situations will affect the formation of SINT-speckles. The formation of inducible SINT-speckles is regulated by several mechanisms, as schematically shown in Figure 9B.…”
Section: Discussionmentioning
confidence: 99%
“…WT mice expressing CD45.1 (∼120 d old) were lethally irradiated (Nanda et al, 2018) and reconstituted with bone marrow cells (2.5 × 10 6 in PBS) via tail vein injection. Following reconstitution, mice received prophylactic antibiotics in their drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…This selective action of TPL2 on specific MAPKs is intriguing and should expand the utility of this target for several indications (see below). Recent studies with catalytically inactive ABIN2 (D310N) in gut inflammation showed that ABIN2 regulates IL-1β-dependent induction of cyclooxygenase 2 (COX2) and PGE2 secretion 189 , functions previously thought to be regulated by TPL2 (ref. 190 ).…”
Section: Mapk: Tpl2 P38γ P38δ and Erk5mentioning
confidence: 99%